On the Response of Zhejiang Coastal Waters to 12 Typhoons from 2011 to 2015 - Yunhe Pan; Anzhou Cao; Yuqian Wu; Shiming Lu; Luteng Fan; Peiliang Li (Journal of Marine Science and Engineering, 2022)
Based on the hybrid coordinate ocean model (HYCOM) reanalysis data, the dynamical and thermal response of Zhejiang coastal waters to 12 typhoons from 2011 to 2015 was studied, and the relationship between the oceanic response and typhoon characteristics was analyzed. The HYCOM reanalysis data were validated by satellite-observed sea surface temperature data. Results show that all the 12 typhoons caused near-inertial waves, sea surface cooling and seafloor warming, but significant differences existed among them. Based on statistics, it was found that the domain-averaged near-inertial kinetic energy and seafloor warming are significantly correlated with the typhoon’s maximum wind speed, both of which show a positive relationship. The domain-averaged seafloor warming also decreases with the typhoon’s translation speed. Moreover, there exists a positive correlation between the domain-averaged sea surface cooling and seafloor warming. The different mechanisms that caused the seafloor warming for the 12 typhoons were also investigated in this study.